The 4-Octahedra model - Abarca Morales, Edgar (Frontiers in Materials, 2024)
This work comprises a generalisation of a simple geometric model devel- oped to describe coupled rotations of corner-sharing octahedra in the surface layer of Sr2RuO4 under uniaxial compression [1]. The main objective of the model is to establish a link between the experimental, global strain configu- ration, and the possible microscopic mechanisms and compatible geometries by which the octahedra accommodate the applied strain. In achieving this, a useful and intuitive parametrisation of 4-site two-dimensional systems of corner-sharing octahedra has been established, which can be readily extended to three-dimensions and N > 4 inequivalent sites, or directly employed to anal- yse the octahedral configuration of many perovskites, transition metal oxides and layered compounds.